ORMDL3 and allergic asthma: From physiology to pathology - James, Briana (J Allergy Clin Immunol, 2019)
There is a strong genetic component to asthma, and numerous genome-wide association studies have identified ORM1 (yeast)–like protein 3 (ORMDL3) as a gene associated with asthma susceptibility. However, how ORMDL3 contributes to asthma pathogenesis and its physiologic functions is not well understood and a matter of great debate. This rostrum describes recent advances and new insights in understanding of the multifaceted functions of ORMDL3 in patients with allergic asthma. We also suggest a potential unifying paradigm and discuss molecular mechanisms for the pathologic functions of ORMDL3 in asthma related to its evolutionarily conserved role in regulation of sphingolipid homeostasis. Finally, we briefly survey the utility of sphingolipid metabolites as potential biomarkers for allergic asthma.